Comparison of Maternal Serum Calcium Level Between Preeclamptic and Normotensive Pregnancies (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: The pathophysiology of preeclampsia remains poorly understood despite having many studies. The association of decreased calcium level Preeclampsia (PE) has been proposed for decades. This study aimed to compare serum total calcium levels between women with preeclampsia and normotensive pregnant women at a tertiary care teaching hospital in Bangladesh. Materials and methods: One hundred pregnant women with a gestational age of more than 28 weeks and singleton pregnancy [50 preeclamptic (Cases) women and 50 normotensive pregnant women (Control)] were included in the selected case-control study from the Obstetrics & Gynecology Department of Chittagong Medical College Hospital. On admission, venous blood samples were collected before the commencement of treatment. Serum total calcium levels were estimated and compared between the two groups. Results: Out of 50 cases, 23 (46%) had preeclampsia without severe features and 27 (54%) had preeclampsia with severe features. The mean (± standard deviation) serum level of calcium in the control group, PE patients without severe features and PE patients with severe features were 9.14±0.48 mg/dl, 8.31±0.59and 8.29±0.61mg/dl, respectively. The meanserum total calcium level was significantly lower in preeclamptic patients with severe features and preeclamptic patients without severe features than the normotensive women (p